A new method of deriving the acceleration and displacement design spectra of pulse-like ground motions based on the wavelet multi-resolution analysis. Issue 119 (April 2019) - Zhao, Guochen; Xu, Longjun; Gardoni, Paolo; Xie, Lili
Abstract: Pulse-like ground motions usually have higher spectral displacements and spectral accelerations than other motions in long periods and can cause severe damage on structures. However, there is still no a generally accepted method to incorporate the features of this type motion in the code-based design spectrum. The pulse period is one of the key parameters to characterize the features of pulse-like ground motions. The relations between the pulse period and the earthquake magnitude have been well studied, and many prediction equations have been proposed. However, these results cannot be considered in the process of deriving the design spectrum of pulse-like ground motions. This paper proposes a new method to derive the acceleration and displacement design spectra of pulse-like ground motions based on the wavelet multi-resolution analysis. To consider the influence of the frequency content of ground motions, the frequency band of ground motions is divided into several continuous sub-bands. One or more ground motion components obtained by the wavelet multi-resolution analysis are used to represent the frequency content in each sub-band. Differing from previous methods, the design spectral shape of the proposed method can be changed according to the frequency content of ground motions, and the prediction equations between the pulse period and the earthquake magnitude can be used to improve the current code-based design spectrum. Highlights: A new method of deriving the design spectra of pulse-like ground motions is proposed. Design spectral shape can be changed according to pulse feature. The predicted pulse period can be used to improve the code-based design spectra. Both acceleration and displacement design spectra are considered.